Diatom-Bacteria Interactions Modulate the Composition and Productivity of Benthic Diatom Biofilms - Koedooder, Coco; Stock, Willem; Willems, Anne; Mangelinckx, Sven; De Troch, Marleen; Vyverman, Wim; Sabbe, Koen (Frontiers in Microbiology, 2019)
Benthic diatoms are dominant primary producers in intertidal mudflats and constitute a major source of organic carbon to consumers and decomposers residing within these ecosystems. They typically form biofilms whose species richness, community composition and productivity can vary in response to environmental drivers and their interactions with other organisms (e.g. grazers). Here, we investigated whether bacteria can affect diatom community composition and vice versa, and how this could influence the biodiversity-productivity relation. Using axenic experimental communities with three common benthic diatoms (Cylindrotheca closterium, Navicula phyllepta and Seminavis robusta), we observed an increase in algal biomass production in diatom co-cultures in comparison to monocultures. The presence of bacteria decreased the productivity of diatom monocultures while bacteria did not seem to affect the overall productivity of diatoms grown in co-cultures. The effect of bacteria on diatom growth, however, appeared to be species-specific, resulting in compositional shifts when different diatom species were grown together. The effect of the diatoms on the bacteria also proved to be species-specific as each diatom species developed a bacterial community that differed in its composition. Together, our results suggest that interactions between bacteria and diatoms residing in mudflats are a key factor in the structuring of the benthic microbial community composition and the overall functioning of that community.